Methods of Increasing the Role of Ethno-Cultural Values in Ensuring Youth Spirituality and Social Activity against "Mass Culture" - Rahmonova Sanoat Shuhrat kizi (International Journal on Integrated Education, 2023)
The role of ethnocultural values in the fight against "popular culture". The role of national values in preventing the negative consequences of popular culture.